Analysis of Network Demand and Research on the Key Technology for Integration of 5G and Wi-Fi - Ming Liu; Zhizhong Zhang; Fang Cheng (Dianxin kexue)
The integration network of 5G and Wi-Fi can well solve the problem of rapid growing wireless traffic and user experience pursuit in 5G. Integration of multi-radio access technology, multiple needs and multiple internet were studied to become the inevitable trend for IMT 2020（5G）. In the networking of 5G and Wi-Fi, integration of network application scene and fusion networking technology were introduced to be the inevitable demand, no-sense authentication, network security, green communication were proposed to become the key technical indicators.